REALITAS SOSIAL DALAM KUMPULAN CERITA PENDEK AKU BENCI TETAPI TUHAN TIDAK KARYA ANI NI’MATUL KHUSNA DKK. - Nama Penulis, Nama Penulis (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2023)
This study aims to find a problem of social reality in the short story collection I Hate But The Lord Was Not The Work of Ani Ni’matul Khusna with her colleagues. Methods used in this research is descriptive qualitative method. This research includes the type of qualitative research. The source of this research is a collection of short stories. The data collection technique used is the technique of read and record. The data in this study were analysed using the approach of the sociology of literature. Variety of social reality faced by the public, such as poverty, crime , disorganization of the family, the problems of the younger generationin modern society, the violation of the norms of society and the population problem. Based on the the results of research in the short story collection I Hate But The Lord Was Not The Work of Ani Ni’matul Khusna with here colleagues, found it to social reality existing on the issue of poverty, crime, disorganization of the family, the problems of the younger generation in modern society, the problem of population describes about the life of the social reality of the community. Keywords : reality, social, short story, sociology